PENINGKATAN HASIL BELAJAR IPAS SISWA KELAS V SDN 2 TALESAN DENGAN PENERAPAN MODEL PEMBELAJARAN PJBL MELALUI MEDIA DIODRAMA - Anita Cahyani (Jurnal Jaringan Penelitian Pengembangan Penerapan Inovasi Pendidikan (Jarlitbang), 2023)
The science learning results in the Food Chain material for class V students at SDN 2 Talesan, totaling 16 children, were deemed to be very poor, especially in the science subject. Some students' grades and activity in class are still lacking and below the KKM. This research aims to improve the science and science learning outcomes of fifth grade students at SDN 2 Talesan using the PJBL (Project Based Learning) learning model through the Food Chain Diodrama props. The research used the Classroom Action Research method in two cycles. The subjects of this research were fifth grade students at SDN 2 Talesan, Odd Semester, 2023/2024 Academic Year. The learning outcomes assessed are cognitive, affective and psychomotor skills measured by test results, student observation instruments and field notes at the end of each cycle. The results of the analysis show that the science and science learning outcomes of class V students at SDN 2 Talesan increased, as indicated by the increase in the average grades and student activities from cycle I to cycle II. The application of the PJBL (Project Based Learning) learning model through Diodrama teaching aids provides positive results for the learning outcomes of class V students at SDN 2 Talesan.